Prevalence of Asthma and Associated Factors at Zewditu Memmorial Hospital Emergency Department, Addis Ababa, 2017g.c. - Lehulu Tilahun (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background Asthma results significant health problem on individuals and clinical facilities. Methods Hospital based retrospective cross sectional study was conducted. Data was collected from patient record, who visited adult emergency room from February 1, 2016 to February 1, 2017. Finally it was analyzed with SPSS Version 20 and presented in tables and graphs. Results From total 120 patients studied 55 (45.8%) were males and 65(54.2%) being females and producing a 0.84 to 1.0 of male to female. Magnitude of Asthma produced as 1.5%. On average, respondents’ age was 46.73 with standard Deviation of 17.5. Among respondents, 61(50.8%) affected with allergen, 21(17.5%) because of asthma, 13(10.8%) because of drug adherence and 25(20.8%) because of activities done and depression. Conclusion There was a low prevalence of asthma with no sex difference. The dominant symptoms found from the study subjects were wheezing, dyspnea and cough.